Wet‐Chemical Processing of Phosphorus Composite Nanosheets for High‐Rate and High‐Capacity Lithium‐Ion Batteries. Issue 10 (30th March 2016) - Zhang, Yanyan; Rui, Xianhong; Tang, Yuxin; Liu, Yaqing; Wei, Jiaqi; Chen, Shi; Leow, Wan Ru; Li, Wenlong; Liu, Yuanjun; Deng, Jiyang; Ma, Bing; Yan, Qingyu; et al.
Abstract : Phosphorus‐based materials are promising for high‐performance lithium‐ion battery (LIB) applications due to their high theoretical specific capacity. Currently, the existing physical methods render great difficulty toward rational engineering on the nanostructural phosphorus or its composites, thus limiting its high‐rate LIB applications. For the first time, a sublimation‐induced synthesis of phosphorus‐based composite nanosheets by a chemistry‐based solvothermal reaction is reported. Its formation mechanism involves solid–vapor–solid transformation driven by continuous vaporization–condensation process, as well as subsequent bottom‐up assembly growth. The proof‐of‐concept LIBs composed of the phosphorus‐based nanosheets achieve a high capacity of 630 mAh g −1 at an ultrahigh current density of 20 A g −1, which is attributed to efficient lithium‐ion diffusion and electron transfer. Such simple sublimation‐induced transformation opens up new prospects for rational engineering of phosphorus‐based materials for enhancing electrochemical performance. Abstract : A sublimation‐induced synthesis strategy has been developed to form holey phosphorus‐based composite nanosheets by a chemistry‐based solvothermal reaction. As proof‐of‐concept, the phosphorus composite nanosheets electrodes can achieve a high capacity of 630 mAh g −1 at ultrahigh current density of 20 A g −1 .